Constructing a fashion managerial skills competency framework in Small-Medium Enterprise fashion business in Malaysia - Kamarulzaman, Zulina (2023)
Entrepreneurs in the fashion industry face significant challenges in acquiring and practicing business skills and competencies. The purpose of this study is to identify the skill requirements that fashion design entrepreneurs (FDE) need to succeed in a competitive business environment. Having a diverse set of skills is essential for FDE to ensure the efficient functioning, stability, and long-term success of the company. This study adopted a qualitative methodology in which fashion experts assessed a series of questions. The data collection process involved virtual focus group discussions, interviews, and question-and-answer sessions with fashion design entrepreneurs, established fashion industry professionals, and government employees who support and train FDEs. Study data were analysed using NVivo12 software to extract codes and themes that led to the final results, and descriptive analysis was performed using SPSS statistical software. This study identifies five essentials for successful business management: mastering personal leadership, competent design management, competent financial management, efficient human resource management, and strong networking skills. The importance of the elements is emphasised. The Fashion Design Entrepreneurs' Managerial Sustainability Framework (FDEMARS) research framework was developed based on key findings. The research framework was validated by a group of 30 fashion-related industry experts, including fashion design entrepreneurs, academic experts specialising in fashion and textiles, as well as industry representatives. The validation process yielded positive results. Experts agreed that FDEMARS is a comprehensive and effective tool for FDEs of different business ability levels. In conclusion, this paper highlights the importance of incorporating business skills management into the FDE function to improve effectiveness and address the various issues faced by the country's economic fashion industry.